2018
DOI: 10.1007/s00586-017-5458-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of unexpected positive histology in kyphoplasty

Abstract: Therefore, we could demonstrate that the incidence of unexpected positive histology in vertebral compression fracture treated with kyphoplasty is significant (3.1%). As a conclusion, if a kyphoplasty is performed due to assumed osteoporotic vertebral compression fracture, a biopsy should be taken to safely rule out a pathological fracture caused by lymphatic bony invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…In our study, the biopsy results of three patients were positive and the filing of a possible malpractice suit was prevented. Of note, in our series, 13 pathology reports included insufficient material; however, this is consistent with the literature (15), and is also legally safe for the clinician because of the biopsies (14).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the biopsy results of three patients were positive and the filing of a possible malpractice suit was prevented. Of note, in our series, 13 pathology reports included insufficient material; however, this is consistent with the literature (15), and is also legally safe for the clinician because of the biopsies (14).…”
Section: Resultssupporting
confidence: 89%
“…These authors also reported on the specific increase of neurosurgical medicolegal cases (12). Nowak et al suggested that the incidence of positive histology in PBK is high and, if no biopsy is taken, malpractice will be alleged (14). In our study, the biopsy results of three patients were positive and the filing of a possible malpractice suit was prevented.…”
Section: Resultssupporting
confidence: 55%
“…Other investigations reported significantly higher incidence rates of unsuspected malignancy in biopsies during vertebroplasty and came to similar conclusions [9]. Hansen [10][11][12][13]. Based on their results, Li et al further analyzed the economic burden due to routine biopsy.…”
Section: Resultsmentioning
confidence: 57%
“…One study did not report on the modality of preoperative imaging. Studies combining a bone scan with an MRI had unexpected malignancies in 1–3% only [ 11 , 18 , 19 ], compared to 0.4–6% in studies using an MRI [ 8 , 10 , 12 17 , 20 , 21 ], and 6% in the one study reporting on unexpected lesions using CT only [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biopsy is not performed routinely with these procedures based on the hypothesis that most VCFs are secondary to osteoporosis. However, it is well established that VCFs secondary to malignancy are a relatively common etiology as well 8–10 . Although the exact incidence of malignancy varies based on the study quoted, it has been reported to be as high as 10% to 15% 9,11,12 …”
mentioning
confidence: 99%